Calcium stabilizes the strongest protein fold - Lukas F. Milles (Nature Portfolio, 2018)
Staphylococcal pathogens adhere to their human targets using adhesins, which can withstand extremely high forces. Here, authors use single-molecule force spectroscopy to determine the similarly high unfolding forces of B domains that link the adhesin to the bacterium.